β-Galactosidase: Immunological Activity of Ribosome-Bound, Growing Polypeptide Chains - Hamlin, Joyce (1972)
Ribosomes carrying nascent chains of β-galactosidase were prepared by disruption of Escherichia coli in detergent-free buffer of high salt concentration, followed by purification on a discontinuous sucrose gradient. Assay by the method of immune hemolysis inhibition with anti-β-galactosidase indicated that considerable amounts of antibody were bound by the growing chains. Much of the crossreacting material could be released from the ribosomes by treatment with puromycin. The ability to bind anti-β-galactosidase was completely destroyed when ribosomes were heated at 60°C. At very early times after induction, well before the appearance of active enzyme, crossreacting material could be demonstrated on ribosomes; this finding correlated with the appearance of an amino-terminal fragment of β-galactosidase. Thus, growing chains of β-galactosidase must begin to fold before their release from the ribosome.